Innovation of Shampoo Bar From Natural Herbal Essential Oil of Aceh - Syaifullah Muhammad; Retika Septi Diana Utari; Masykur Rahmatullah; Habil Fadhlurrahman; Farid Muhammad Arie; Tia Amanda; Friesca Erwan; Raihan Dara Lufika; Ernawati Ernawati (Journal of Patchouli and Essential Oil Products, 2022)
According to 2020 data from the Indonesian Ministry of Environment and Forestry explained that 38.3% of waste in Indonesia is waste from households and 17.1% of the total waste is plastic waste. The use of bar shampoo can help reduce plastic bottle waste derived from liquid shampoo in order to go green movement. NEUBA-Natural Essential Oil Shampoo Bar is a shampoo made from natural ingredients in the form of patchouli oil and aloe vera extracts with a bar-shaped appearance. NEUBA contains patchouli oil which is one of Aceh's essential oils that are already very well-known on the international scene. The constituent components that have the largest percentage are patchouli alcohol (32.60%), guaiene (23.07%), guaiene (15.91%), seychellena (6.95%), and patchoulena (5.47%) (Yunilawati and Endeh, 2016). As well as for the ingredients used are patchouli oil, Aloe Vera Extract, Sodium Cocoyl Isethionate, Cocamidopropyl Betaine, Cocoa Butter, Cetyl Alcohol, D-Panthenol, Citric Acid, Phenoxyethanol, Green Tea, Mica powder. The overall activities were come out of the laboratory of Atsiri Research Center (ARC) of Syiah Kuala University (USK). This shampoo bar innovation product has the potential as a new product that is environmentally friendly, practical and uses natural ingredients that are potential local resources.